AHP-TOPSIS: Multi-Criteria Decision Making Method With Hierarchical Weighting to Determine Priorities for Leak Work Drinking Water Pipe - Muzdalifah, Lilik; Nursiyami, Sutanti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to develop an effective multi-criteria decision making method by paying attention to the validity of the criteria weighting. In previous research, the TOPSIS method was applied to the problem of determining priorities for repairing drinking water pipe leaks by paying attention to four (4) criteria, namely the duration of the complaint, the size of the leak, the leak point, and the distance from the leak point to the location of the officer handling the leak.. The research results show that the TOPSIS method has a simple concept and is able to provide priority recommendations for the order of work based on consumer complaints. However, in this research the results of decision making were considered not optimal because the TOPSIS method for calculating criteria weights did not yet have a hierarchical mediator that guaranteed the validity of the criteria weightings. Therefore, this research tries to combine two methods (AHP-TOPSIS), namely Analytical Hierarchy Process (AHP) and Technique for Order Performance by Similarity to Idea Solution (TOPSIS). AHP is a Multi Criteria Decision Making (MADM) method that can be used to determine criteria weights hierarchically, with a smooth order of levels and considering the relationship between criteria. In this research, AHP was used to obtain criteria weights and TOPSIS to rank priorities for work on drinking water pipe leaks. The research results show that AHP-TOPSIS can produce a more effective and valid rating to help solve the problem of determining priorities for working on drinking water pipe leaks. This solution is the best decision where work priorities are selected based on criteria that are in accordance with service priorities.